2021
DOI: 10.3389/fbioe.2021.797939
|View full text |Cite
|
Sign up to set email alerts
|

Salix spp. Bark Hot Water Extracts Show Antiviral, Antibacterial, and Antioxidant Activities—The Bioactive Properties of 16 Clones

Abstract: Earlier studies have shown that the bark of Salix L. species (Salicaceae family) is rich in extractives, such as diverse bioactive phenolic compounds. However, we lack knowledge on the bioactive properties of the bark of willow species and clones adapted to the harsh climate conditions of the cool temperate zone. Therefore, the present study aimed to obtain information on the functional profiles of northern willow clones for the use of value-added bioactive solutions. Of the 16 willow clones studied here, 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 93 publications
(121 reference statements)
1
9
0
Order By: Relevance
“…This study provides baseline knowledge and proof-of-concept for the further development of antimicrobial, biobased functional coatings, and protective materials by valorizing the side streams of forestry industries, focusing on the condensed tannin-rich extract of Norway spruce bark as a case study. Similar value-added phenolics can also be obtained from other wood species or plant biomasses, such as willows, as shown in our earlier study ( Tienaho et al, 2021 ) and those by ( Lohtander et al, 2020 ; Lohtander et al, 2021 )…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This study provides baseline knowledge and proof-of-concept for the further development of antimicrobial, biobased functional coatings, and protective materials by valorizing the side streams of forestry industries, focusing on the condensed tannin-rich extract of Norway spruce bark as a case study. Similar value-added phenolics can also be obtained from other wood species or plant biomasses, such as willows, as shown in our earlier study ( Tienaho et al, 2021 ) and those by ( Lohtander et al, 2020 ; Lohtander et al, 2021 )…”
Section: Discussionsupporting
confidence: 85%
“…Tests were conducted according to the procedure described earlier ( Tienaho et al, 2021 ). In brief, the constitutively luminescent light signal emitting bacterial biosensor strains E. coli K12+pcGLS11 and S. aureus RN4220+pAT19 were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These strains have been constructed to produce a constant luminescent light signal and antibacterial effects can be observed as a loss of emitted light signal intensity. The storage, cultivation, and test protocol has been previously described [36,44]. In brief, the strains were stored at −80 • C and awoken by approximately 16 h cultivation at 30 • C (for E. coli) and 37 • C (for S. aureus) in lysogeny agar plates (tryptone 10 g/L; yeast extract 5 g/L; NaCl 10 g/L; and agar 15 g/L).…”
Section: Antibacterial Efficacymentioning
confidence: 99%
“…29 Notably, secondary metabolites found in such biomass are known for their multifaceted properties, encompassing antioxidant, antibacterial, antiviral, antihyperglycemic, antihypertensive and antiproliferative properties. [30][31][32] Given the extant evidence on the health and technological benets of ingredients and natural preservatives, biorenery potential and alternative valorisation techniques have been explored to replace synthetic antioxidants with plant-derived bioactive compounds. Evidence has shown that hemp fractions can provide natural antioxidants and anti-inammatory nutritional support.…”
Section: Introductionmentioning
confidence: 99%